Identification of novel host-parasite interactions of Plasmodium falciparum using a dual epitope monoclonal antibody - Schwake, Christopher. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisors: Athar Chishti, and James Baleja.; Committee: Karl Munger, and John Castellot.; Keywords: Biology, and Parasitology.